CORRELATION OF SUBJECTIVE GLOBAL ASSESSMENT SCORE WITH TOTAL LYMPHOCYTE COUNT AMONG TUBERCULOSIS PATIENTS: HUBUNGAN SKOR SUBJECTIVE GLOBAL ASSESSMENT DENGAN KADAR LIMFOSIT TOTAL PADA PASIEN TUBERKULOSIS - Meriza Martineta; Dina Keumala Sari; Andika Pradana; Hilna Khairunnisa Shalihat; Aida Siregar (Faculty of Medicine Universitas Islam Sumatera Utara, 2026)
Malnutrition and tuberculosis (TB) have a bidirectional relationship, in which poor nutritional status contributes to impaired immune function and disease progression. Subjective Global Assessment (SGA) is a validated clinical tool for nutritional assessment, while total lymphocyte count (TLC) reflects immune competence. This study aimed to investigate the correlation between SGA score and TLC among tuberculosis patients. A descriptive cross-sectional study was conducted among 34 adult TB patients attending the tuberculosis clinic at Universitas Sumatera Utara Teaching Hospital between October and December 2025. Nutritional status was assessed using SGA, and TLC values were obtained from medical records. Data were analyzed using Spearman’s rank correlation test. The median TLC was 1,873.64 cells/µL (range 742.72–9,874.23). Based on SGA classification, 29.4% of patients were well nourished, 44.1% were moderately malnourished, and 26.5% were severely malnourished. A statistically significant moderate positive correlation was observed between SGA score and TLC (r = 0.40; p = 0.019). Conclusion: There was a significant positive correlation between SGA score and TLC in tuberculosis patients. These findings highlight the importance of comprehensive nutritional assessment as part of integrated tuberculosis management to identify patients at risk of immune impairment.